The Role of Polyphenol Oxidase (PPO) in Antiprolactin Activity - Sabir, Dlawer M.; Putros, Basima Y. (Sulaimani Journal for Pure and Applied Sciences, 2004)
The role of polyphenoi oxidase which has been extracted from Mellssia officinalis and purified by gel filtration and ion exchange chromatography rn'as tested on phenolic compounds such as: chlorogenic acid and catechol to decrease the level of proiactin. Similarly the effect of l00mg of freeze-dried exhact of the plant and I 00mg of 20% oxidation products of freeze-dried extract have been studied. The rnost effective treatment, was the enz)rme trealnlent, which had reduced the prolactin 1evel fram3.372 nglrnl to 1.7644 ng/ml .This reveals that such products, which rvere formed by the enzyme action on the substrates catechol and chlorogenic acid couldbe used to reduce the proiactinby individuals who suffer from hyperprolactinemia ,It is rvell hrown that hypelprolactinemra reduces libido sexual impotence and infertility in men.
Keywords: polyphenol oxidase antiprolaetin acivityMelissia officinalis